Moral injury and original sin: The applicability of Augustinian moral psychology in light of combat trauma - Powers, Brian S. (Theology today, 2017)
Veterans of the conflicts in Iraq and Afghanistan often experience moral injury as an ambiguous sense of guilt or deep confusion or annihilation of a sense of what is good and right. Augustine argued that as personal agents, our willing follows that which we desire--the problem is that our desires are externally and internally distorted and our willing thus follows goods that are twisted and false. I argue that an Augustinian framework of human willing in pursuit of distorted goods holds a great deal of explanatory power in terms of the pathology of human violence and the phenomenon of moral injury in combat veterans. As several prominent psychological studies suggest, evolutionary, societal, and cultural forces condition our capacity to make critical moral decisions. Those studying moral injury in combatants have observed the profound guilt that eventually results from their participation in acts of violence and even in support of missions whose moral "good" they come to question. An Augustinian framework recognizes both the power of these external forces and the distortable nature of our own moral values and therefore allows us to locate moral injury in the realm of systemic, widespread societal and cultural problems. This definition allows the experience of differing levels of participation in wartime violence from "front-line combat" to support missions to be understood as valid experiences of moral injury while simultaneously recognizing that one's active agency is required in order to experience moral injury. Further, this framework may resonate with veterans who experience hopelessness as a result of reflection on the malleability of human willing and its profound vulnerability to outside forces.